PENDAMPINGAN BELAJAR SISWA MELALUI PENDALAMAN MATERI DAN FUN GAMES DI DESA KEDUNGUTER, KABUPATEN BANYUMAS - Miza Liyana Bte Moh Warid; Rima Oktavia Kusuma (Abdi Jaya : Jurnal Pengabdian Indonesia, 2025)
This community service activity aims to improve elementary school students' learning comprehension through learning assistance in the form of in-depth material and fun games in Kedunguter Village, Banyumas District. The activity was held on August 8, 17, 24, and 31, 2021, at the Jenderal Soedirman University (Unsoed) Community Service Post in Kedunguter Village. Participants were elementary school students residing in RT 03 RW 02, with a total of 4–8 students. The implementation method included direct learning assistance, delivering material tailored to students' needs, and incorporating educational games to increase learning motivation. The results showed an increase in students' understanding of the subject matter and an increased interest and enthusiasm for learning. However, there were obstacles in the form of consistent absences from some students. Overall, this activity had a positive impact on the children's learning process and served as an alternative learning assistance during online school implementation.